Thermal Barrier Coatings on Laser Surface Modified AISI H13 Tool Steel Using Atmospheric Plasma Spray Technique - Reza, M. S.; S. N., Aqida; Mohd Toff, Mohd Radzi; Brabazon, D. (Trans Tech Publications, Switzerland, 2013)
This paper presents yttria-stabilized zirconia (YSZ) coating deposition on laser surface modified H13 tool steel using atmospheric plasma spray (APS) technique. A Praxair Plasma Spray System with SG-100 gun was used to deposit coating materials on laser-modified H13 tool steel substrate surface. A bond coat layer material was NiCrAlY alloy while the top coat was yttria stabilized zirconia (YSZ) with powder size distribution range of -106 µm to +45 µm. A 23 design of experiment (DOE) was used to deposit bond coat and top coat powders with three controlled factors of input current, powder feed rate and stand-off-distance. The design was optimised for minimum porosity and maximum hardness. The coating thickness and percentage of porosity were measured using IM7000 inverted optical microscope. Hardness properties of top coating layer were measured by using MMT-X7 Matsuzawa Hardness Tester Machine with vickers hardness scale. The microscopy findings indicated variations of coating thickness at different parameters settings. Samples at the highest current and powder feed rate and lowest stand-off distance settings produced a lower porosity percentage and higher hardness. A higher powder feed rate with the smallest stand-off-distance allowed melted powders to travel uniformly onto the substrate surface. These findings were significant to development of thermal barrier coatings on semi-solid forming die surface.